2017
DOI: 10.1016/j.jcin.2017.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Presentation, and Predictors of Clinical Restenosis in Coronary Bioresorbable Scaffolds

Abstract: The 3-year incidence of ScR was similar to that observed in similar settings with newer-generation drug-eluting stents. It is often associated with a benign presentation and a complex angiographic pattern. Predictors of ScR match those of metallic stent restenosis, and the implantation technique used at index appears to play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…Our finding of comparable mortality rates in BVS-treated and EES-treated patients replicates the observations of other recent BVS clinical studies[9,[31][32][33], even though we cannot exclude that the present study may lack statistical power to detect differences in rare events such as death. Related to increased TVR and TV-MI events in the BVS group, our results are consistent with that of Wykrzykowska et al[28]; however, the role of additional factors not detectable by propensity-matching should be taken into account, including: a lower decisional threshold for performing angiographic follow-up in the BVS group especially during the earlier clinical experience and after complex revascularizations, and the higher rate of incomplete revascularizations in the BVS group due to the devicespecific technical limitations (e.g., treatment of bifurcations with twostent techniques)[34]. Our finding of an increased risk of deviceFIG URE 2 Kaplan-Meier curves for event-free survival from DoCE (composite of cardiac death, target-vessel related myocardial infarction and clinically driven target-lesion revascularization), in patients with small vessel coronary artery disease treated with BVS compared to EES controls.…”
supporting
confidence: 91%
“…Our finding of comparable mortality rates in BVS-treated and EES-treated patients replicates the observations of other recent BVS clinical studies[9,[31][32][33], even though we cannot exclude that the present study may lack statistical power to detect differences in rare events such as death. Related to increased TVR and TV-MI events in the BVS group, our results are consistent with that of Wykrzykowska et al[28]; however, the role of additional factors not detectable by propensity-matching should be taken into account, including: a lower decisional threshold for performing angiographic follow-up in the BVS group especially during the earlier clinical experience and after complex revascularizations, and the higher rate of incomplete revascularizations in the BVS group due to the devicespecific technical limitations (e.g., treatment of bifurcations with twostent techniques)[34]. Our finding of an increased risk of deviceFIG URE 2 Kaplan-Meier curves for event-free survival from DoCE (composite of cardiac death, target-vessel related myocardial infarction and clinically driven target-lesion revascularization), in patients with small vessel coronary artery disease treated with BVS compared to EES controls.…”
supporting
confidence: 91%
“…A number of previous publications, including those of our group, reported that device and procedural parameters including vessel size, use of pre-and postdilation, device to reference vessel diameter ratio, are major predictors of events up to three years [5][6][7][8][9][10][11][12]22,23]. The current data suggest that only diabetes, a well-known risk factor for late events after stenting [24], is a determinant of very long-term outcome, and that the incidence of outcomes is independent of device/procedural characteristics.…”
Section: Predictors Of Early and Late Eventsmentioning
confidence: 85%
“…For the successful use of polymer‐based BRS, two things seem to be very important: (1) a scaffold‐specific implantation technique with high pressure postdilatation and (2) an adequate lesion preparation . Accordingly, when following these recommendations, clinical results are not significantly inferior when comparing ABSORB BVS™ and DES . It is unknown, if these results would be the same for Magmaris™.…”
Section: Discussionmentioning
confidence: 99%
“…Despite high procedural success rates and favorable early outcome studies, recent large‐scale randomized controlled trials showed an increased rate of early and late device thrombosis when comparing first‐generation polymer‐based Absorb BVS™ (Abbott Vascular, Santa Clara, CA, USA) to 2nd generation DES . It is commonly assumed that the high event rate may be partially explained by the fact that in initial studies, operators were not aware of the importance of following a strictly standardized implantation protocol that mandates thorough lesion preparation and high‐pressure postdilatation with appropriately sized balloons . Also, the avoidance of lesions with a small reference diameter was postulated to improve results .…”
Section: Introductionmentioning
confidence: 99%